2023
DOI: 10.3390/app13074313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultrashort Pulsed Direct Laser Writing on Ni/Al Reactive Multilayer Foils

Abstract: Reactive multilayer foils (RMFs) for joining processes have attracted a great deal of attention over the last few years. They are capable of exothermic self-propagating reactions and can serve as localized heat sources for joining applications when ignited by suitable means. Using short and ultrashort pulsed lasers with carefully selected parameters, cutting and shaping of RMFs makes it possible to tailor heat release characteristics without triggering the reaction. The present study is an investigation of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Martins et al investigated the effect of different femtosecond laser parameters on the heataffected zone of a NI/AL-based RMF. The result showed that the HAZ was considerably small for all the tested parameters, thereby indicating no heat agglomeration [19]. Le et al investigated the effects of three key parameters, the angle of incidence, FPB-FIB distance, and scanning speed, on the feed laser drilling process.…”
Section: Introductionmentioning
confidence: 99%
“…Martins et al investigated the effect of different femtosecond laser parameters on the heataffected zone of a NI/AL-based RMF. The result showed that the HAZ was considerably small for all the tested parameters, thereby indicating no heat agglomeration [19]. Le et al investigated the effects of three key parameters, the angle of incidence, FPB-FIB distance, and scanning speed, on the feed laser drilling process.…”
Section: Introductionmentioning
confidence: 99%